Opportunities and challenges for commercializing microarray patches for vaccination from a MAP developer's perspective. Issue 4 (30th November 2022) - Forster, Angus; Junger, Michael
ABSTRACT: Continued advances in microarray patch (MAP) technology are starting to make needle-free delivery of a broad range of vaccines an achievable goal. The drivers and potential benefits of a MAP platform for pandemic response and routine vaccination are clear and include dose-sparing, cold-chain elimination, increased safety, and potential self-administration. MAP technology is regarded as a priority innovation to overcome vaccination barriers, ensure equitable access, and improve the effectiveness of vaccines. Vaxxas, a global leader in this technology, has built a strong evidence-base for the commercial application of their high-density (HD) MAP platform, and is rapidly advancing scale-up of the manufacturing process for HD-MAPs. A greater awareness and understanding of the implications of the technology amongst supply-chain participants, regulatory authorities, and global healthcare organizations and foundations is needed to accelerate adoption and, particularly, to prepare for MAP use in pandemics. Key challenges remain in the commercialization of MAP technology and its adoption, including market acceptance, scale-up of production, regulatory approval, and the availability of capital to build advanced manufacturing infrastructure ahead of late-stage clinical trials.